Evaluating the Efficacy of 4-Arylidene-2-phenyl-5-(H)-oxazolones compounds as Potential Antimicrobial Agents Against some Antibiotic-Resistant Strains (Sebha University Conference Proceedings, 2024)
The emergence of antibiotic-resistant bacteria presents a significant challenge in developing effective antimicrobial agents. This study investigates the antibacterial activity of a series of 4-Arylidene-2-phenyl-5(H)-oxazolones, a class of compounds known for their versatility in medicinal chemistry. The synthesis of these compounds was performed according to established protocols, and their antibacterial efficacy was evaluated using broth microdilution and agar well diffusion assays against five bacterial strains, including Pseudomonas aeruginosa, Staphylococcus aureus, Burkholderia Cepacia, E. coli, and Acinetobacter Baumannii. The results demonstrated variable inhibitory effects across the different bacterial strains, with compound A1 showing significant activity against Acinetobacter Baumannii and compound CL1B exhibiting potent inhibition of E. coli and Enterobacter Cloacae. Statistical analysis indicated a trend towards compound specificity, although the differences did not reach conventional statistical significance. The study highlights the potential of 4-Arylidene-2-phenyl-5-(H)-oxazolones as a platform for developing targeted antibacterial agents. The observed variability in antibacterial activity underscores the importance of structural diversity and functional groups in designing effective antimicrobial compounds. Further research is necessary to elucidate these compounds' mechanisms of action and optimize their antibacterial properties for clinical applications.